Creating musical life reviews with older people: a community case study - Gilboa, Avi; Levy, Nomi (Frontiers in Public Health, 2024)
Older people living in their homes might experience growing loneliness, detachment from their social environment, and decreased functional ability. In this community case study, we report on a project we initiated to enhance the functional ability of older people by creating musical life reviews (MLR) with them. We connected seven of our music therapy graduates (MT) to older people living in the neighborhood across the street from campus. MTs were first trained to work by a protocol for creating MLRs with older people, developed by the authors of this article. They then worked with older people from the neighborhood for 10 one-on-one sessions, on personally tailored MLRs. MTs kept on meeting in weekly group supervision sessions, thus learning from each other- and forming a community of their own. Participants expressed their high satisfaction with the process and reported that their MLRs became increasingly important to them. Most of them were interested in taking their MLR one step ahead, and playing it to family and/or friends, and, as part of the process, planned a personal event to do this. Further, two big community events were initiated by participants and MTs. To conclude, we show how the community project enhanced the functional ability of those participating in it. We also point at possible challenges and recommendations for further implementation of the project.